Ethics and Law of Using Blockchain Technology for Electronic Health Records in Indonesia - Prio Agus Santoso, Aris; Soraes, Domingos; Gegen, Geradus; Ayu Sekar Astuti, Oktaviana (LPPM Universitas Duta Bangsa Surakarta, 2024)
In Indonesia, the use of blockchain in the context of electronic health records is still in its early stages. Current regulations are more focused on the application of blockchain in the financial and fintech sectors. Meanwhile, the healthcare sector, especially concerning electronic health records, lacks a clear legal framework for this technology. This situation raises concerns about protecting patient rights and data privacy, which are critical aspects of medical ethics. This research aims to examine the legal and ethical framework related to the use of blockchain technology in electronic health records in Indonesia. The research method employed is a normative legal approach with conceptual and statutory approaches derived from secondary data. The results are then analyzed qualitatively. The findings indicate that blockchain has the potential to revolutionize the management of electronic health records (EHR) in Indonesia, in line with Regulation of the Minister of Health No. 24 of 2022. This technology ensures the security, integrity, and transparency of medical data through permanent, immutable records, adhering to principles of confidentiality and data integrity. Blockchain also enables more accountable access management. However, its implementation must consider ethical issues, including patient privacy and regulatory compliance. With the right approach, blockchain can become a foundation for a secure and trustworthy digital health system in Indonesia.